2009
DOI: 10.1002/jat.1491
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of rosmarinic acid on V79 cells evaluated by the micronucleus and comet assays

Abstract: Rosmarinic acid (RA) is a naturally occurring phenolic compound, which contributes to the beneficial and health-promoting effects of herbs, spices and medicinal plants. RA has shown several biological activities, such as hepatoprotective, anti-inflammatory, antiangiogenic, antitumor, antidepressant, antineurodegenerative, HIV-1 inhibitory and antioxidant effects. The aim of this study was to investigate the ability of RA to prevent chemically induced chromosome breakage or loss and primary DNA damage using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 34 publications
1
32
0
3
Order By: Relevance
“…DNA damage caused by different nitrosoureas has been studied via different methods of detection, such as agarose gel electrophoresis assay [16], fluorescence assay [17] and lipid chromatography/mass spectrometry (LC/MS) [18]. Being highly sensitive and specific, the comet assay proved to be a useful technique to evaluate the degree of DNA damage [19]. Our study compared the interstrand crosslinking induced by different kinds of CENUs via single cell gel electrophoresis (SCGE) assay firstly, and it showed that SCGE assay is a convenient method to detect the DNA breaks and interstrand crosslinks.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage caused by different nitrosoureas has been studied via different methods of detection, such as agarose gel electrophoresis assay [16], fluorescence assay [17] and lipid chromatography/mass spectrometry (LC/MS) [18]. Being highly sensitive and specific, the comet assay proved to be a useful technique to evaluate the degree of DNA damage [19]. Our study compared the interstrand crosslinking induced by different kinds of CENUs via single cell gel electrophoresis (SCGE) assay firstly, and it showed that SCGE assay is a convenient method to detect the DNA breaks and interstrand crosslinks.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment designs and cell collection and fixation procedures described by Furtado et al were used. 15) The criterion proposed by Fenech was used for the analysis of micronuclei. 16) A total of 3000 binucleated cells were scored per treatment, corresponding to 1000 cells/treatment/ repetition.…”
Section: Micronucleus Assaymentioning
confidence: 99%
“…The cells were then washed with PBS, complete culture medium containing cytochalasin-B (Sigma-Aldrich; 3 µg/mL) was added, and the mixture was incubated for 17 h. The cells were harvested and fixed as described by Furtado et al 25) The criterion established by Fenech 26) was used for the analysis of micronuclei in which 3000 binucleated cells were scored per treatment, for a total of 1000 cells/treatment/repetition.…”
Section: )mentioning
confidence: 99%